Stand characteristics, leaf traits and growth of threatened conifer Pilgerodendron uviferum (Cupressaceae) in Southern Patagonia, Argentina - Peri, Pablo Luis; Bahamonde, Hector Alejandro; Toledo, Santiago; Martínez Pastur, Guillermo José (MDPI, 2024)
Pilgerodendron uviferum is an endemic Cupressaceae of Patagonia (Argentina) that is restricted to a small group of individual trees, growing in isolated populations (relicts) along its distribution. The main objective was to evaluate the habitat, forest structure, leaf traits, leaf nutrient reabsorption and growth of four relicts (area between 0.3 and 0.86 ha) in the Santa Cruz province (Argentina) to improve the available information for forest conservation purposes. Principal components analysis was conducted to determine the separation between relict populations based on their ecological characteristics (individual and habitat levels). We found contrasting environmental and forest structure conditions among the four studied relicts. For example, two relicts associated with Nothofagus antarctica showed higher values of P. uviferum tree density, DBH and dominant height at the stand level. Alongside that, these relicts presented a higher sapling density (1950–3167 ind ha−1) and understory plant diversity compared to pure P. uviferum relicts growing near the ecotone with the steppe grassland. Specific leaf area, carbon and nutrient concentrations in P. univerum leaves varied depending on the relict conditions and tree age of the individuals. The mean nutrient resorption efficiency varied according to relicts and particular nutrients, ranging from 18.1% to 49.5% for Ca and P, respectively. The diameter growth of the dominant P. univerum trees ranged from 0.33 to 0.46 mm yr−1, indicating that the species follows a stress-tolerant strategy. The information of this work may assist in the conservation of marginal P. uviferum forest communities spatially disconnected with continuous forests, growing in relicts.